Differential effect of cis-platinum (cis-diamminedichloroplatinum) on regulation of liver and kidney haem and haemoprotein metabolism. Possible involvement of gamma-glutamyl-cycle enzymes. - Maines, M D (1986)
The treatment of rats with cis-platinum (cis-diamminedichloroplatinum) for 1, 3 or 7 days elicited vastly different responses in the liver and the kidney in activities of enzymes of haem-metabolism pathway and gamma-glutamyl-cycle enzymes. The differences resided in the magnitude, direction and the time course of responses. In general, the liver was by far less severely affected, and when a response was elicited, it displayed an earlier onset (1-3 days), with a return to normal at 7 days. In the kidney, however, the effects were notable after 3 days of treatment, and became more pronounced at 7 days. Specifically, the activity of 5-aminolaevulinic acid (ALA) synthetase and contents of cytochrome P-450 and the microsomal haem were decreased in the liver. In contrast, in the kidney, cytochrome P-450 and haem concentrations were significantly increased, with no change in ALA synthetase activity. The increase in the kidney haem content appeared to reflect an increased formation of haem, as suggested by the elevated activity of ferrochelatase and the concomitant decrease in tissue porphyrin levels. In the kidney, a time-dependent and pronounced inhibition of activities of gamma-glutamylcysteine synthetase, the rate-limiting enzyme in glutathione production, and gamma-glutamyl transpeptidase, the first enzyme in glutathione breakdown, were observed. The enzyme activities, 7 days after treatment, were only 40 and 60% of the control values respectively. In contrast, these enzyme activities were not affected in the liver. Complexing cis-platinum with cysteine considerably intensified the entire spectrum of effects of cis-platinum in the kidney. Notably, cytochrome P-450 concentration and haem oxygenase activity were increased to about 3.5 and 6 times the control values, respectively. gamma-Glutamylcysteine synthetase activity was decreased to less than 20% of the control. It is suggested that the differential effectiveness of cis-platinum in the liver and the kidney in alternating haem metabolism is related to the vast differences which exist between these organs in the activities of gamma-glutamyl-cycle enzymes. It is further suggested that this may promote the formation in the kidney, but not in the liver, of a cis-platinum-cysteine complex that is more stable, and thus biologically more effective, than the parent compound.